EVALUATING ALTERNATIVE PRODUCTION STRATEGIES FOR CLAMP SADDLE PRODUCTS TO IMPROVE PROFITABILITY: A CASE STUDY OF PT SENTRA PIPA NUSANTARA - Adityo Ramadhan; Gatot Yudoko (RADJA PUBLIKA, 2026)
The plastic piping industry depends on a complete portfolio of pipes and fittings to serve infrastructure, clean-water distribution, and industrial applications. PT Sentra Pipa Nusantara (a disguised name) completes part of its fitting portfolio through imported products, including the clamp saddle 63 mm × 1¼